Psychological Foundations of the Formation of Leadership and Willpower Qualities in the Personality of Students of Military Education - Sattarovich, Abdusalomov Ulugbek (Indonesian Journal Publisher, 2025)
This study aims to examine the psychological foundations that contribute to the development of leadership and willpower traits in students of military education. The research seeks to identify key psychological theories, methods, and practices that shape these traits in the military learning context. The method employed is a qualitative, normative-descriptive approach supported by literature analysis, with the integration of theories from Kurt Lewin, Albert Bandura, Lev Vygotsky, John Dewey, and Abraham Maslow. The study systematically analyzes military students’ personal development through the lens of motivation, stress resilience, responsibility, and decision-making under pressure. Findings indicate that leadership and willpower are interrelated characteristics cultivated through structured pedagogical practices and psychological interventions such as scenario-based simulations, reflective learning, stress management, and guided mentorship. The use of individualized development plans and experiential learning enhances students’ self-awareness, emotional regulation, and capacity for moral responsibility—traits deemed critical in military service. The research concludes that military education must embed psychological support systems to foster sustainable personal and leadership development among students.